Psychological, social, and mechanical work exposures and disability retirement: a prospective registry study - Jan S. Emberland; Morten Birkeland Nielsen; Stein Knardahl (BMC, 2017)
Abstract Background Relations between several occupational psychological and social factors and disability retirement remain largely unexplored. Knowledge of which specific aspects of the work environment that affect risk of disability is a prerequisite for the success of organizational interventions aiming to prevent premature work force exit. The objective of the present study was to determine contributions to registered disability retirement by a broad range of psychological and social work exposures while taking into account effects of mechanical exposure. Methods Written consent was obtained from 13 012 employees (96 organizations) representing a wide range of occupations, to link their survey responses to data from the Norwegian national registry of disability compensation. Median follow-up time was 5.8 years. To determine effects of self-reported work exposures on risk of disability retirement hazard ratios (HR) and 99% confidence intervals (99% CI) were calculated with Cox regression analysis. Effects of sex, age group, skill level, sickness absence in the last three years, and work exposures estimated to be confounders were accounted for. Post hoc stratification by sex was conducted to explore if identified predictors affected risk of disability retirement differently in men compared to women. Results Contributors to higher risk of disability retirement were "role conflict" (high level HR 1.55 99% CI 1.07 to 2.24) and "physical workload" (high level HR 1.93 99% CI 1.39 to 2.68). Contributors to lower risk of disability retirement were "positive challenge" (high level HR 0.56 99% CI 0.34 to 0.93), "fair leadership" (high level HR 0.56 99% CI 0.39 to 0.81), and "control over work intensity" (high level HR 0.62, 99% CI 0.47 to 0.82). Direction of effects was not dependent on sex in any of the five identified predictors. Conclusions Several specific psychological and social work factors are independent contributors to risk of disability retirement. In order to prevent premature work force exit workplace interventions should consider targeting the predictors identified by the present study.